Insula volumes are altered in patients with social anxiety disorder - Atmaca, Murad; Koc, Mustafa; Mermi, Osman; Korkmaz, Sevda; Aslan, Sabriye; Yildirim, Hanefi (Elsevier B.V., 2021)
Objective: In the present study, we aimed at examining the volumes of the insula in more pure patients with a social anxiety disorder. Methods: We examined twenty-one patients with social anxiety disorder according to DSM-IV and twenty healthy controls. All patients and controls were applied to magnetic resonance imaging (MRI). Insula volumes were measured by using the manual tracing method in accordance with the standard anatomical atlases and related previous studies on insula volumes. Results: We found that the mean posterior and anterior insula volumes for both sides of patients were statistically significantly reduced compared to those of healthy control subjects. Conclusion: Consequently, in the present study, we found that patients with a social anxiety disorder had reduced insula volumes compared to those of healthy control subjects. However, to get strong this finding, novel studies with a larger sample size are required. © 2020
Keywords: Insula volumes; Magnetic resonance imaging; Phobia; Social